Auxin transport during root gravitropism: transporters and techniques. (3rd May 2013) - Geisler, M.; Wang, B.; Zhu, J.
Abstract: Root gravitropism is a complex, plant‐specific process allowing roots to grow downward into the soil. Polar auxin transport and redistribution are essential for root gravitropism. Here we summarise our current understanding of underlying molecular mechanisms and involved transporters that establish, maintain and redirect intercellular auxin gradients as the driving force for root gravitropism. We evaluate the genetic, biochemical and cell biological approaches presently used for the analysis of auxin redistribution and the quantification of auxin fluxes. Finally, we also discuss new tools that provide a higher spatial or temporal resolution and our technical needs for future gravitropism studies.